Educação e cultura popular nas propostas escolares de EJA - Educação de Jovens e Adultos: um estudo em duas escolas de Belo Horizonte - Clarice Wilken de Pinho (2016)
This research analyzed the cultural and educational work that involves what has relation to the expressions of life of whom is popular. The aim was to verify what is being possible to enclose in popular education and culture in different school purposes in Education for the Young and Adult People in Belo Horizonte city. We search identify the involvement of the young and adult students in artistic activities of several kinds linked to their knowledge and cultures. In order to increase our reflexions, we made a recovery of the main education and popular culture movements that appeared in Brazil in the 1960 decade, detaching the purposes developed in four of these movements: Movimento de Cultura Popular (Movement of Popular Culture, in English); Campanha de Pé no Chão Também se Aprende a Ler(something like Campaign Barefoot Also Learn to Read); Movimento de Educação de Base (Movement of Basic Education) e Centro Popular de Cultura( Culture Popular Center). After this serious study we selected two schools that work with Education for the Young and Adult People in Belo Horizonte city, searching to regard different spaces and ways of organization. The choice of these schools started from a previous survey made in database, visits and listening to people involved with the theme Education and Culture in different fields of action: researchers, educators and managers of the area. The attention to the wealth of the cultural experiences that form the multiple identities of the education for the young and adult people was a very important factor for the development of this research. We conclude that to compose a curriculum with the students and not to the students -, establishing a dialogue between their demands and the cultural and educational demands is an important aspect for the respect to the specifities of the people that compose the young and the adult education.